1996
DOI: 10.1111/j.1460-9568.1996.tb01607.x
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine—paracrine Regulation of Hippocampal Neuron Survival by IGF‐1 and the Neurotrophins BDNF, NT‐3 and NT‐4

Abstract: In contrast to sympathetic and sensory neurons in the peripheral nervous system, the neurotrophic requirements for neurons in the central nervous system (CNS) have not been clearly identified. The inactivation of specific neurotrophic factors and their receptors by gene targeting has shown that there are no major changes in neuron numbers in the CNS. This suggests an overlap between the action of different neurotrophic factors in the brain during development. Here we have studied the survival of hippocampal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(113 citation statements)
references
References 63 publications
6
106
0
1
Order By: Relevance
“…It has been reported that NeuroD is an upstream regulator of neurotrophin receptors in the differentiating neurons of inner ear (Kim et al, 2001). In the cerebellum, Trk/neurotrophin signaling is essential for the migration, polarization, and survival of the cerebellar granule cells (Borghesani et al, 2002;Lindholm et al, 1996;Minichiello and Klein, 1996). In the hippocampus, TrkB and TrkC signaling cooperate to promote the survival of the DG granular neurons (Minichiello and Klein, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that NeuroD is an upstream regulator of neurotrophin receptors in the differentiating neurons of inner ear (Kim et al, 2001). In the cerebellum, Trk/neurotrophin signaling is essential for the migration, polarization, and survival of the cerebellar granule cells (Borghesani et al, 2002;Lindholm et al, 1996;Minichiello and Klein, 1996). In the hippocampus, TrkB and TrkC signaling cooperate to promote the survival of the DG granular neurons (Minichiello and Klein, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…30 Thus, within the hippocampus, neurons from the BDNF knockout mice exhibited enhanced cell death compared with cells from the wild-type animals. 27 Moreover, exogenous BDNF increased the survival of the hippocampal neurons lacking BDNF. 27 BDNF prevents the spontaneous death of dopaminergic neurons in rat primary mesencephalic cultures 31,32 and protects TH-immunoreactive neurons from the selective toxin MPP þ (1-methyl-4-phenylpyridinium).…”
Section: Bdnf Gives Trophic Support To a Variety Of Cns Neuronsmentioning
confidence: 98%
“…27 Moreover, exogenous BDNF increased the survival of the hippocampal neurons lacking BDNF. 27 BDNF prevents the spontaneous death of dopaminergic neurons in rat primary mesencephalic cultures 31,32 and protects TH-immunoreactive neurons from the selective toxin MPP þ (1-methyl-4-phenylpyridinium). 29 Repeated intrastriatal injections of BDNF protect from damage induced by intrastriatal administration of 6-OHDA, 33 with moderate preserving of striatal dopaminergic nerve endings around the injection site.…”
Section: Bdnf Gives Trophic Support To a Variety Of Cns Neuronsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although IGF receptor ligands increased survival, apoptosis still occurred in approximately 50% of bcl-x 7/7 cells grown in supplemented media, suggesting that additional factors may promote survival of E12 bcl-x 7/7 telencephalic cells. The effects of a number of neurotrophic factors were tested using concentrations of factors shown previously to have maximal effects on other neuronal cells (Ip et al, 1994;Lin et al, 1993;Lindholm et al, 1996;Knusel et al, 1990;Widmer and Hefti, 1994). Addition of 50 ng ml 71 nerve growth factor (NGF), 25 ng ml 71 brain-derived neurotrophic factor (BDNF), 25 ng ml 71 neurotrophin (NT)-3, 25 ng ml 7 1 NT-4, 25 ng ml 71 ciliary neurotrophic factor (CNTF), 25 ng ml 71 glial-derived neurotrophic factor (GDNF), or 25 ng ml 71 epidermal growth factor (EGF) did not increase bcl-x 7/7 telencephalic cell survival (data not shown).…”
Section: Igf Receptor Ligands Promote Telencephalic Cell Survival Indmentioning
confidence: 99%